Building the bridge: outlining steps toward an applied sleep-and-memory research program - Feld, Gordon Benedikt; Diekelmann, Susanne (Current directions in psychological science, 2020)
Sleep’s beneficial role for memory is well documented, yet the translation of such fundamental memory processes into applications for improving memory function is limited so far. Although there are some commercial devices with varying levels of technical complexity that are claimed to improve sleep-dependent memory processing, none of them have been empirically validated. The main issue seems to be that there is basically no applied research in the field of sleep and memory. To change this, we identify the most promising targets for sleep-based memory-improvement applications. We outline the theoretical and technical aspects of the most promising memory-enhancing sleep interventions established in recent years and highlight potential targets of such interventions for different healthy and clinical populations. Finally, we propose a unifying framework that will lay the groundwork for a focused applied-research program in sleep and memory, bridging the gap between basic research and targeted application.
Online veröffentlicht: 2. November 2020
Gesehen am 23.05.2024